2000
DOI: 10.1159/000015510
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new TSPY gene family member in Yq (TSPYq1)

Abstract: We investigated subinterval 6E on the human Y chromosome, a region frequently deleted in infertile males. YAC yOX17, mapped within subinterval 6E by STS-PCR, was analyzed for the presence of new genes. TSPYq1, a member of the TSPY multi-copy gene family, was isolated and character- ized from a yOX17 cosmid subclone. PCR and FISH analysis performed on normal subjects and on patients with microdeletions of Yq suggested the presence of multiple copies of TSPY in Yq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…1] and yOX97, yOX232 [not shown]). Since yOX40 lies in interval 6C, TSPYE must be distinct from TSPYq1 found by Ratti et al (2000) to be located in interval 6E, which we now designate TSPYF. Thus there are at least four loci on Yp and two on Yq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1] and yOX97, yOX232 [not shown]). Since yOX40 lies in interval 6C, TSPYE must be distinct from TSPYq1 found by Ratti et al (2000) to be located in interval 6E, which we now designate TSPYF. Thus there are at least four loci on Yp and two on Yq.…”
Section: Resultsmentioning
confidence: 99%
“…FISH analysis revealed an additional minor locus on Yq11.23 (Schempp et al, 1995). Recently, a new member of the TSPY gene family (TSPYq1) (GenBank accession number AF106331) was isolated from subinterval 6E, part of the AZFc region (Ratti et al, 2000). Thus, in humans, as in many other species, TSPY is organized as a repetitive gene family, with interindividual variation in copy number ranging from about 30 to 60.…”
mentioning
confidence: 99%
“…Transposition of individual genes and groups There is evidence that gene translocation has been a relatively common event in the history of the TTY2 genes; at least two clusters of genes occur: a large group on Yq (AZFc), and a smaller one on Yp. The gene multiplicity and clustering shown by the TTY2 family is a feature shared with other male-specific, Y-linked gene families, such as RBMY (Chai et al 1997), DAZ (Saxena et al 1996), and TSPY (Manz et al 1993;Vogel and Schmidke 1998;Ratti et al 2000), which are also arranged in tandemly arrayed clusters on both arms of the Y chromosome. It is notable that the location of the TTY2-like genes coincides with the location of two TSPY gene clusters in both arms of the Y chromosome (Arnemann et al 1991;Vogt et al 1987;Ratti et al 2000).…”
Section: The Tty2 Gene Familymentioning
confidence: 91%
“…The gene multiplicity and clustering shown by the TTY2 family is a feature shared with other male-specific, Y-linked gene families, such as RBMY (Chai et al 1997), DAZ (Saxena et al 1996), and TSPY (Manz et al 1993;Vogel and Schmidke 1998;Ratti et al 2000), which are also arranged in tandemly arrayed clusters on both arms of the Y chromosome. It is notable that the location of the TTY2-like genes coincides with the location of two TSPY gene clusters in both arms of the Y chromosome (Arnemann et al 1991;Vogt et al 1987;Ratti et al 2000). It has been suggested that the region containing TSPY on Yp is particularly prone to chromosomal rearrangements, and contains many tandemly repeated sequences (Müller et al 1989).…”
Section: The Tty2 Gene Familymentioning
confidence: 91%
See 1 more Smart Citation